Highly distinguishable isomeric states of a tripodal arylazopyrazole derivative on graphite through electron/hole-induced switching at ambient conditions - Himani Malik; Sudha Devi; Debapriya Gupta; Ankit Kumar Gaur; Sugumar Venkataramani; Thiruvancheril G. Gopakumar (Beilstein Journal of Organic Chemistry, 2025)
Manipulating the energy barrier and extending the half-life of nonequilibrium states in photochromic switches presents viable solutions for applying them in molecular electronics. Typically, the half-life of the Z isomer of azobenzene (AB) is a few days. Arylazopyrazole-based molecular switches are one of the profoundly explored systems in recent times due to their superior bidirectional photoswitching and long half-life (over a thousand days at room temperature) of Z isomers. Herein, we utilize an efficient solid-state photoswitchable fluorinated tripodal N-functionalized arylazo-3,5-dimethylpyrazole derivative (FNAAP) to envisage and access multiple metastable states on the surface. The tripodal molecule forms well-ordered, large crystalline domains on graphite through non-bonding interactions between the molecules. By injecting electron/hole pairs into the self-assembled molecules on a surface using a scanning tunneling microscope (STM) tip, they are switched between 8 states (EEE, EEZ, EZE, ZEE, EZZ, ZEZ, ZZE and ZZZ) in a tunneling junction at ambient conditions. Contrary to the degeneracy-controlled four states in solution phase, all the eight states are remarkably stable on the surface and are well distinguishable by the tunneling current passing through the molecule at the tunneling junction. The change in current upon switching between these states is approximately an order of magnitude. This is particularly notable at positive sample voltage compared to negative sample voltage. The exceptional stability of the states at ambient conditions provides an opportunity to use a single FNAAP molecule as an 8-bit operation unit, with a potential storage capacity of ≈200 Tbits per 1 cm2 area using an atomically precise write and read tool like an STM tip.